A new species of Nanophyllium Redtenbacher, 1906 from the northern coast of New Guinea (Phasmida, Phylliidae) - Cumming, Royce T. (Zootaxa, 2016)
A new species of leaf insect, Nanophyllium stellae n. sp. is described and illustrated. As for the majority of the current taxa of Nanophyllium Redtenbacher, 1906, the new species is named from a single male specimen, as no other specimens are currently known to exist. A key to the current species of Nanophyllium Redtenbacher, 1906 is provided. The holotype was photographed using a Canon 5D Mark II and a MP-E 65mm macro lens and will be deposited in the San Diego Natural History Museum. Photos were stacked using Zerene photo stacking software, version 1.04, 64-bit. Measurements of anatomical figures were made to the nearest 0.1 mm. Currently, only four species of Nanophyllium Redtenbacher, 1906 have been described, all from males, with N. stellae n. sp. marking the fifth species. To date, there have been no females described, save one possible N. hasenpuschi Brock & Grösser, 2008 specimen illustrated from Nabire, Irian Jaya (Brock & Hasenpusch, 2003).